Monitoring and prediction of air quality system using internet of things (IoT) - Alrubaye, Mohammed Saad Ashraf; As’arry, Azizan; Azman, Muhammed Amin; Mohamed Yusoff, Mohd Zuhri; Md Rezali, Khairil Anas; Zolfagharian, Ali (Semarak Ilmu Publishing, 2025)
Air pollution is a global issue causing 7 million deaths annually, primarily due to dangerous compounds and inhalable particles. The World Health Organization estimates that air pollution is a significant threat to human health and safety. The Internet of Things (IoT) is utilized in this research to analyse sensor data from various environmental monitoring devices. The objective is to build an IoT-based air quality system that assesses air quality conditions in specific areas and analyses air levels of various compounds. The study employs IoT technology to analyse data from various environmental sensors, aiming to create an IoT-based air quality system. The sensors include measuring NH, C6H6, VOCs (MQ135), CH4 (MQ5), and particle matter (PM2.5). The ESP32 microcontroller and thinger.io platform is used to develop the system. FastTree and Generalized Additive Model (GAM) are machine learning methods applied to predict and analyse air quality data. FastTree utilizes gradient-boosting to enhance accuracy, while GAM employs smooth parts, represented by splines, for relationship modelling. Evaluation metrics R2, RMSE, MSE, and MAE assess model performance, for MQ135 with FastTree outperforming GAM with an R2 of 91.91% compared to 78.05%. The IoT-based air quality system is user-friendly and effective, tracking harmful components against thresholds. Future work includes adding cameras and printed circuit boards for expanded analysis.